A Review on Pharmaceutical Potential of Parthenium Plant - Ravi, Dr. Lokesh (Asian Journal of Pharmaceutics (AJP), 2020)
Parthenium plant, in general, is known to be harmful, dangerous, and invasive in nature. It causes much economic loss to farmers by affecting the cultivation of crops and considered to be a threat to primary production of crops and biodiversity as well. Parthenium hysterophorus a weed belonging to the family Asteraceae, it is an erect short-lived plant and is known for its fleshy growth along sides of abandoned places, roadsides, and uncultivated lands. This weed is found in hot and humid climates around the globe. This invasive species is known with different names in different countries such as carrot weed, star weed, congress grass, wild feverfew, ragweed, bitter weed, and white top. The spread of P. hysterophorus has been found to cause enormous loss to biodiversity by replacing natural ecosystems and sometimes known to cause total habit alternation. In this review article, we discuss P. hysterophorus as a weed, its origin, reproductive bionomics, chemical composition, and its pharmaceutical potential as antibacterial, anti-inflammatory, hypoglycemic, anti-HIV, and antitumor activity in detail.